2022
DOI: 10.3390/jmse10081068
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Freshwater Calcifiers to Carbon-Dioxide-Induced Acidification

Abstract: Increased anthropogenic carbon dioxide (CO2) in the atmosphere can enter surface waters and depress pH. In marine systems, this phenomenon, termed ocean acidification (OA), can modify a variety of physiological, ecological, and chemical processes. Shell-forming organisms are particularly sensitive to this chemical shift, though responses vary amongst taxa. Although analogous chemical changes occur in freshwater systems via absorption of CO2 into lakes, rivers, and streams, effects on freshwater calcifiers have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…A recent synthesis of 22 predominantly laboratory‐based CO 2 ‐enrichment studies on freshwater microalgae found that elevated CO 2 generally lowers pH and increases DIC, algal productivity and nutrient uptake, but growth responses vary by algal type and sometimes between species of the same type (Brown et al., 2020; Hu & Gao, 2008). CO 2 ‐enrichment studies on freshwater invertebrates have primarily focused on direct effects (e.g., behavior, acidification effects on calcification), mostly via single‐species laboratory experiments (e.g., Hasler et al., 2017; Ninokawa & Ries, 2022; Ramaekers et al., 2022). In some cases, invertebrates have been studied in laboratory microcosms containing algae (or leaf litter; see Alto et al., 2005), allowing assessment of indirect invertebrate responses.…”
Section: Introductionmentioning
confidence: 99%
“…A recent synthesis of 22 predominantly laboratory‐based CO 2 ‐enrichment studies on freshwater microalgae found that elevated CO 2 generally lowers pH and increases DIC, algal productivity and nutrient uptake, but growth responses vary by algal type and sometimes between species of the same type (Brown et al., 2020; Hu & Gao, 2008). CO 2 ‐enrichment studies on freshwater invertebrates have primarily focused on direct effects (e.g., behavior, acidification effects on calcification), mostly via single‐species laboratory experiments (e.g., Hasler et al., 2017; Ninokawa & Ries, 2022; Ramaekers et al., 2022). In some cases, invertebrates have been studied in laboratory microcosms containing algae (or leaf litter; see Alto et al., 2005), allowing assessment of indirect invertebrate responses.…”
Section: Introductionmentioning
confidence: 99%
“…Although the effect of rising atmospheric CO 2 on ocean acidification and hence marine calcifying organisms has elicited substantial concern (Andersson et al., 2008; Kawahata et al., 2019; Kleypas et al., 1999), the potential impact to freshwater calcifiers from increasing pCO 2 atm has only recently been addressed (Ninokawa & Ries, 2022). Rising atmospheric CO 2 increases the carbonic acid concentrations (H 2 CO 3 *) of surface waters according to Henry's Law (i.e., aH2normalCO3=KnormalCO2pCO2atm ${a}_{{\mathrm{H}}_{2}\mathrm{C}{\mathrm{O}}_{3}^{\ast }}={K}_{\mathrm{C}{\mathrm{O}}_{2}}\text{pC}{\mathrm{O}}_{2}^{\text{atm}}$), which subsequently dissociates to HCO 3 − and H + , shifting the carbonate buffer system toward HCO 3 − as CO 3 2− reacts with H + (Orr, 2011; Orr et al., 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Unlike the ocean, freshwater systems are commonly undersaturated with respect to aragonite and calcite. Hence, freshwater calcifying organisms can tolerate substantially lower carbonate mineral saturation states than marine calcifiers (Ninokawa & Ries, 2022). Nevertheless, the much lower alkalinity and pH buffering capacity of freshwater systems compared to the ocean can still negatively impact freshwater calcifiers (Ninokawa & Ries, 2022), especially as rising atmospheric CO 2 drives these systems to progressively lower saturation states with respect to carbonate minerals (Beaune et al., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations